(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Lignin preparations, introduced into soil jointly with buckwheat Fagopyrum esculentum Moench, variety 'Aiva' (cultivated throughout Latvia) seeds during the sowing in quantities of 20 kg ha-1 and 40 kg ha-1, exerted a favourable effect on the ned in alcohol extracts from the biomass of different morphological parts of buckwheat, were represented mainly by rutin. The content of rutin in the ethanol extracts from the biomass of flowers with bract reached the maximum values in the phase of accomplishing blooming - beginning of fruit formation to be 2.74% in terms of dry mass (exceeding the rutin content development of plants and the synthesis of flavonoids in flowers with bract. Flavonoids, determin the control by 65%) in the variant with 40 kg ha-1 of Lignosilicon. Lignin preparations favoured the increase in the radical scavenging capacity of the alcohol extracts of the biomass of flowers with bract of buckwheat, as well as grain and hulls. The increment of the buckwheat grain crop, in comparison with the control on the background of 40 kg ha-1 of lignin, was 12%, and that on the background of 20 kg ha-1 and 40 kg/ha of Lignosilicon 10% and 15%, respectively.